Selective adsorption of Au3+ from aqueous solutions using persimmon powder‐formaldehyde resin. Issue 6 (3rd July 2013) - Xie, Feng; Fan, Zaijun; Zhang, Qinglin; Luo, Zhengrong
ABSTRACT A new adsorption resin has been developed by immobilizing persimmon powder with formaldehyde, and its adsorption properties to Au3+ were investigated in detail. The resin exhibited outstanding selective adsorption capacity towards Au3+ from acidic aqueous solutions (pH 2.0), which the equilibrium adsorption capacity was high up to 3025.20 mg g−1 at 323 K. The resin exhibited 100% adsorption of Au3+ within 8 h, and the experimental data were well fitted with the pseudo‐first/second‐order rate model. The adsorption isotherms could be well described by Freundlich equation. The column studies suggested that the resin was effective for the adsorption of Au3+ from aqueous solutions, and the loaded Au3+ could be easily desorbed by acidic thiourea solution. The adsorption of Au3+ was an endothermic reductive adsorption process. This suggested that the resin can be used as an active biosorbent for the recovery of Au3+ from aqueous environment. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 3937–3946, 2013